Say Goodbye to Mildew and Save Energy Home Study Course – Part II: Moisture the Culprit – How It Gets Into Your Home - Virginia Peart (EDIS)
This document is FCS 3212, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: September 2002. First published in December 1990 by the Florida Energy Extension Service. Reviewed: September 2002.